Investigate the effect of lift-off on eddy current signal for carbon steel plate - Faraj, Moneer A.; Fahmi, Samsuri; Abdalla, Ahmed N.; Damhuji, Rifai; Khairudin, Ali; Al-Douri, Y. (EDP Sciences, 2018)
In this study, the effect of various factors like lift-off and depth defect on the eddy current signal was investigated. Investigation methods like response surface methodology (RSM) and composed central design (CCD) were employed to establish the relationship between lift-off distance, depth of a defect and the eddy current signal by the two-factor interaction equation, and would provide a reference in further to accurate the depth defect. The regression analysis suggested that eddy current signal was well fitted by the two-factor interaction equation (R2 = 0.9656). The eddy current signal was investigated by varying the levels of these two independent variables, in which all have significant influences on eddy current signal. There would be a change in the amplitude and when lift-off distance is altered, and lift off distance increased, the increase of the amplitude of output signal decrease gradually.